Glycoprotein 110, the Epstein-Barr virus homolog of herpes simplex virus glycoprotein B, is essential for Epstein-Barr virus replication in vivo. - Herrold, R E (1996)
The Epstein-Barr virus (EBV) glycoprotein gp110 has substantial amino acid homology to gB of herpes simplex virus but localizes differently within infected cells and is essentially undetectable in virions. To investigate whether gp110, like gB, is essential for EBV infection, a selectable marker was inserted within the gp110 reading frame, BALF4, and the resulting null mutant EBV stain, B95-110HYG, was recovered in lymphoblastoid cell lines (LCLs). While LCLs infected with the parental virus B95-8 expressed the gp110 protein product following productive cycle induction, neither full-length gp110 nor the predicted gp110 truncation product was detectable in B95-110HYG LCLs. Infectious virus could not be recovered from B95-110HYG LCLs unless gp110 was provided in trans. Rescued B95-110HYG virus latently infected and growth transformed primary B lymphocytes. Thus, gp110 is required for the production of transforming virus but not for the maintenance of transformation of primary B lymphocytes by EBV.